THE ROLE AND IMPORTANCE OF ORGANIZATIONAL AND ECONOMIC MECHANISMS IN THE DEVELOPMENT OF THE TOURISM INDUSTRY OF UZBEKISTAN (Conferencea, 2024)
According to the World Tourism Organization, 10 per cent of the turnover of the production and services market on our planet is contributed by the tourism sector. According to the results of the analysis, by 2024, the income from international tourist trips is expected to increase. This means that the world is trying to make more and more effective use of tourism. This indicator is expected to proliferate in our country.